Pengaruh Model Pembelajaran Kooperatif Tipe Scramble Terhadap Kemampuan Menulis Kalimat Tunggal Berpola SPOK Siswa Kelas III SDN 066653 Medan. - Anggriani, Fuzi; Hatmi, Edizal; Nurmayani; Sidik Siregar, Fajar; Marselina Sembiring, Masta (STKIP Subang, 2026)
The low ability of students in writing simple sentences with the SPOK (Subject, Predicate, Object, Complement) pattern was identified as a problem in Indonesian language learning at grade III of SDN 066653 Medan. This study aimed to determine students’ ability after the implementation of the Scramble cooperative learning model and to analyze its effect on students’ ability to write simple sentences with the SPOK pattern. This research employed a quantitative approach with a quasi-experimental design. The sample consisted of class III-A (23 students) as the control class and class III-B (25 students) as the experimental class. The research instruments included pretest and posttest consisting of 13 items, supported by observation and interview results. The findings revealed that the average posttest score of the experimental class (80,56) was higher than that of the control class (73,57). The hypothesis testing showed that the calculated t-value (2,454) was greater than the t-table value (2,013), indicating that was rejected and Ha was accepted. These findings were strengthened by observation results showing increased student participation up to 96% and interview results indicating that students found it easier to understand and write sentence elements in a structured manner. Therefore, the Scramble cooperative learning model was proven to be effective in improving students’ ability to write simple sentences with the SPOK pattern at grade III of SDN 066653 Medan.